Numerical Optimization of ZnO Electron Transport Layer and Absorber Properties with Temperature Effects in Germanium-Based Perovskite Solar Cells Using SCAPS-1D Simulation - Sanni, Dahiru M.; Ndanusa, Hadiza H.; Abubakar, Hamza (FUDMA Journal of Sciences, 2026)
Perovskite solar cells (PSCs) have made significant advances in power conversion efficiency (PCE); however, their commercial viability remains hindered by stability concerns with organic transport layers and the environmental toxicity of lead-based absorbers. This study investigates a lead-free germanium-based perovskite solar cell (CH3NH3GeI3) with inorganic charge transport layers of zinc oxide ZnO and copper iodide CuI as electrons and holes transport layers, respectively, using SCAPS-1D simulation. The device design consists of FTO/ZnO/ CH3NH3GeI3/CuI/Au in a standard n-i-p configuration. Key parameters were extensively optimized, including absorber layer thickness (300-800 nm), absorber layer bandgap (1.2-1.6 eV), ZnO electron transport layer (ETL) thickness (10-400 nm), and ZnO bandgap (2.0-4.0 eV). The results show that an optimal absorber thickness of 500-600 nm and an optimal bandgap of 1.4-1.5 eV produce a maximum PCE of about 24.9%. While differences in ZnO thickness have little effect on open-circuit voltage (Voc) and fill factor (FF), parasitic absorption causes small reductions in short-circuit current density (Jsc) and PCE. Increasing the ZnO bandgap improves device transparency while modestly improving performance. Temperature analysis (290-360 K) shows a considerable decrease in Voc, FF and PCE as temperature increase, whereas Jsc remains almost constant, indicating recombination dominated thermal degradation in Ge-based PSCs. Overall, this study demonstrates that optimizing inorganic transport layers and absorber layer can significantly increase the efficiency and stability of lead-free PSCs, providing valuable insights for creating environmentally friendly and thermally robust solar systems.